1994
DOI: 10.1093/hmg/3.9.1565
|View full text |Cite
|
Sign up to set email alerts
|

Monoallelic expression of normal mRNA in the PIT1 mutation heterozygotes with normal phenotype and biallelic expression in the abnormal phenotype

Abstract: The combined deficiency of thyrotropin, growth hormone and prolactin, caused by PIT1 abnormality manifests in the homozygous or heterozygous state. We studied a patient having an allele with Arg271Trp mutation, which produces clinical symptoms in heterozygotes by a dominant-negative effect. However, in the family, her father, grandmother and aunts had the same mutation without clinical symptoms, although the proband had typical phenotypic expression. We analyzed the PIT1 transcript in peripheral lymphocytes by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 0 publications
0
34
0
1
Order By: Relevance
“…Most cases with R271W were sporadic and there were only two familial cases with this mutation. Okamoto et al (11) reported the first family with R271W. They described a patient who was heterozygous for this mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases with R271W were sporadic and there were only two familial cases with this mutation. Okamoto et al (11) reported the first family with R271W. They described a patient who was heterozygous for this mutation.…”
Section: Discussionmentioning
confidence: 99%
“…However, surprisingly, in contrast to a previous report that this mutant acted as a dominant inhibitor of wild type Pit-1 to activate the promoter of GH gene (9), R271W did not inhibit the effect of the wild type on the promoter of GH gene as well as PRL gene, and could activate these promoters to a level similar to wild type Pit-1, at least in our experimental conditions. These results, and the existence of healthy carrier with this mutation (11), suggest that further investigation will be needed to clarify how R271W leads to CPHD.…”
Section: Introductionmentioning
confidence: 94%
“…Among 51 Severe Cases, 44 were IGHD (24 male and 20 female) and 3 were GH-1 gene mutations (one case: type IA (6.7 kb deletion); two cases: type II (point mutation of intron 3; IVS3 + 5G ® A, IVS3 + 5G ® C)) [6,7], 2 were Pit-1 gene mutation [8], and 2 were achondroplasia (Table 1). Hypochondroplasia, Turner syndrome, and chronic renal failure were not included, and complications of other diseases causing growth failure were not observed.…”
Section: ) Etiologies and Clinical Characteristics Of 51 Severe Casesmentioning
confidence: 99%
“…A herança pode ser autossômica recessiva, causada por mutações em homozigose ou heterozigose composta, que produzem vários graus de perda de ligação ao DNA ou perda da ativação da transcrição (31,32,(34)(35)(36)40,45). A herança também pode ser autossômica dominante, causada por mutações em heterozigose, porque a proteína mutante tem uma afinidade aumentada pelos sítios promotores de GH e PRL, causando um efeito dominante negativo sobre a proteína normal (33,38,41,46,47). A mutação R271W em heterozigose é de longe a mais freqüente e ocorre em um dinucleotídeo CpG, provável motivo da freqüente recorrência.…”
Section: Pit-1unclassified